MARJINALISASI (PUBLIK) AKTIVIS DALAM LITERATUR PUBLIC RELATIONS - Kusumaningtyas, Nurhidayati (Universitas Negeri Yogyakarta, 2015)
AbstractActivism can involve an individual or a collection of a few people. The practice of activism is often perceived as negative and destructive actions. In the literature of public relations, we will discover how the activist group pressure group categorized into the